Le religieux comme vecteur d’étude du haut Moyen Âge : perspectives d’enquête pour l’hagiographie et la liturgie - Blennemann, Gordon (Théologiques : revue interdisciplinaire d’études religieuses, 2019)
Cet article propose d’explorer l’importance du phénomène religieux comme vecteur de compréhension du monde médiéval. Dans une perspective d’enrichissement de l’échange entre les disciplines intéressées par le phénomène religieux, il souhaite familiariser les étudiants et les chercheurs en dehors du champ de l’histoire médiévale avec quelques tendances passées et actuelles de la recherche, notamment des travaux intéressés par une étude du religieux à l’intersection du politique et du social. En complément de ces observations préliminaires, l’article trace quelques pistes de réflexion pour les champs de recherche de l’hagiographie et de l’histoire du culte des saints et celui de l’histoire de la liturgie, en focalisant sur le haut Moyen Âge occidental.

Antiques vierges et nouvelles normes. L’hagiographie comme discours normatif chez les bénédictines de Metz (IXe-XIe siècle) - Blennemann, Gordon (Cahiers de civilisation médiévale. Xe-XIIe siècle, 2024)
Cet article propose d’aborder la question de l’implication des communautés de femmes de Metz dans les mouvances de réforme en Lorraine du ixe et surtout du xe siècle et xie siècles, par le biais des récits hagiographiques et, dans une moindre mesure, historiographiques. Ces communautés sont au nombre de trois : Sainte-Glossinde, Saint-Pierre-aux-Nonnains et Sainte-Marie-aux-Nonnains. L’article part de l’hypothèse que ces récits constituent autant de contributions à une communauté discursive débattant, en contexte de réforme, de la définition de la vita religiosa féminine. Les démarches argumentatives adoptées par leurs auteurs recourent entre autres à des modèles de vie ascétique très anciens, notamment celui des vierges et matrones à vocation ascétique de l’Antiquité tardive.
ISBN: 9782490783168 Number: 265
Keywords: Antiquité tardive; Carolingiens; Lorraine; Metz; Saint-Pierre-aux-Nonnains; Sainte-Glossinde; Sainte-Marie-aux-Nonnains; hagiographie; monachisme féminin; réforme lotharingienne

Croyances et pratiques sociales dans les sermons de Césaire d’Arles - Blennemann, Gordon (RELIER : revue interdisciplinaire d’études religieuses, 2023)
En dialogue avec des recherches récentes menées sur les identités multiples des chrétiens de l’Antiquité tardive, cette contribution propose un cas d’étude sur les sermons adressés au peuple de l’évêque gaulois Césaire d’Arles (vers 470-542), plus précisément sur ceux dans lesquels Césaire aborde les pratiques de ses contemporains face à l’abondance d’enfants et l’infertilité, leurs pratiques de guérisons et leurs cultures festives en lien, notamment, avec les fêtes des saints. Miroirs de situations communicationnelles précises, ces sermons permettent de saisir, malgré leur aspect rhétorique, les tensions existant entre le discours épiscopal de Césaire traitant des enjeux de pastorale et de pouvoir épiscopal d’une part, et l’adhésion des chrétiens à des pratiques sociales, jugées incompatibles avec une identité chrétienne d’autre part. Ces sermons montrent en filigrane l’existence d‘une opposition entre deux modèles d’organisation de références identitaires : un modèle pyramidal qui classe toutes les références identitaires par rapport à la seule christianité versus un modèle latéral de ces mêmes références qui suppose qu’en fonction de situations quotidiennes concrètes, la christianité revêtait, pour les croyants, une importance variable. Ce cas d’étude ne permet pas seulement de souligner l’importance d’un regard scientifique équilibré sur les croyances et les pratiques, mais aussi les limites d’une classification de pratiques jugées tantôt religieuses, tantôt sociales.

Le nécrologe du livre du chapitre de l’abbaye Saint-Pierre-aux-Nonnains de Metz (BNF lat. 10028) Commentaire et édition - Blennemann, Gordon (École nationale des chartes, 2009)

Die Metzer Benediktinerinnen im Mittelalter: Studien zu den Handlungsspielräumen geistlicher Frauen - Blennemann, Gordon (Matthiesen Verlag, 2011)

Altestamentarische Modelle für den populus christianus: Hrabanus Maurus' Kommentar zu den Makkabäerbüchern 1 und 2 - Blennemann, Gordon (Vom Blutzeugen zum Glaubenszeugen?: Formen und Vorstellungen des christlichen Martyriums im Wandel, 2014)

Eine Bildurkunde aus dem Benediktinerinnenkloster Sainte-Glossinde in Metz. Zugleich ein Beitrag zur mediävistischen Bild- und Objektwissenschaft - Blennemann, Gordon (Konstanz und Wandel: religiöse Lebensformen im europäischen Mittelalter, 2016)
Section: 1 v. (280 pages) : illustrations ; 25 cm

Vom Blutzeugen zum Glaubenszeugen ? : Formen und Vorstellungen des christlichen Matyriums im Wandel - Blennemann, Gordon; Herbers, Klaus (Franz Steiner verlag, 2014)
In zahlreichen Glaubenskontexten gilt das individuelle oder kollektive Selbstopfer als unüberbietbarer Weg, Grundüberzeugungen durch das Blut als Opferleistung zu besiegeln. Im Christentum werden so die Märtyrer zu wichtigen Zeugen vor Gott, stehen sie doch in der Schar der Heiligen an erster Stelle. Die Autorinnen und Autoren des E-Books widmen sich vor diesem Hintergrund dem Martyrium als historischem Phänomen. Die epochenübergreifende Perspektive richtet den Blick auf die Ursachen seiner langfristigen Wirkmächtigkeit als Denkfigur. Die spätantiken Grundlagen von Martyriumskonzeptionen und deren Tradition und Vermittlung in Mittelalter und Neuzeit werden ebenso untersucht wie Wandlungsprozesse in der Darstellung der Figur des Märtyrers. Denn über dessen Bedeutung als personifiziertes Glaubensideal bestand über Jahrhunderte hinweg Konsens, auch wenn der Märtyrer gerade in Konfliktsituationen von konkurrierenden Parteien als Leitfigur instrumentalisiert werden konnte. So eröffneten sich vielfältige Perspektiven der Adaption und Rekontextualisierung des Martyriums, die in den einzelnen Beiträgen ergründet werden.
Section: 1 vol. (319 p.) ; 24 cm.

Autour des Rogations : création, pratiques et communautés (Ve-VIe siècles) - Couture, Béatrice (Université de Montréal, 2024)
This study delves into the history of the Rogation feast, examining its origin, evolution and role in the creation of community identity in 5th and 6th century Gaul. Adopting a cross-approach between history and anthropology highlights the importance of this ritual for the communities of the period and the narrative surrounding it, as orchestrated by the bishops of Gaul and by various actors. By examining the corpus of sources relating to the first Rogations at this period, we discover how this feast served as an apotropaic ritual and collective penance to cope with various difficulties, such as epidemics and droughts, first in the Rhone valley and then throughout Gaul. Thus, the narrative surrounding this festival and how it fostered community adhesion are at the heart of this study. Broader questions, such as the development of collective practices including fasts, prayers and processions, and the way in which the Rogation narrative connected with biblical origins and became rooted in the episcopal sphere, are also put forward. These observations lead us to conclude that this festive ritual, as a testing ground for all social classes, served as a vehicle for creating stronger, more enduring communities. Indeed, it forged a sense of belonging through shared practices and experiences, resulting in the creation of a conventus and an ecclesiological consensus. Nevertheless, this vision is primarily that of the bishops, and as this study is also concerned with individual and community experiences, therefore we also analyze the feast as a space for negotiation and conflict. In short, this research sheds light on how this ritual went beyond its initial role to become an essential element of Gaul’s cultic landscape. It offers a fascinating insight into how Rogations shaped community identity and served as a catalyst for social cohesion in a crucial period of Christian history in Gaul.
Accepted: 2024-02-23T19:35:13Z
Keywords: =CL; Burgundian Kingdoms; City; Cité; Communautés; Communities; Culture festive; Early Middle Ages; European studies / Études européennes (UMI : 0440); Festivities; Gaul; Gaule; Haut Moyen Âge; Merovingian Kingdoms; Rogations; Royaume burgonde; Royaume mérovingien

De la narration à l'interprétation : la fonction des exempla virginaux dans l'œuvre d'Aldhelm - Binette, Virginie (Université de Montréal, 2023)
Near the end of the 7th century, in the anglo-saxon world, Aldhelm of Malmesbury published his opus geminatum, the Prosa and Carmen de uirginitate. He dedicated his work to the nuns of the double monastery of Barking, particularly the abbess Hildelith. The De uirginitate is a treaty on virginity, which includes a theoretical part and catalogs of virginal figures found in hagiographical as well as in Biblical sources. Historiography has tended to underestimate the role of these catalogs within the treaty, portraying them as a mere florilegium without logic. This dissertation will propose that the virginal figures mentioned in the catalogs served as exempla. More specifically, we propose that these characters are exemplary figures whose function is to mirror the theoretical part of the De uirginitate. Ald-helm’s treaty will then appear to possess a double function, which is to defend the double monas-teries and the nuns’ authority in an increasingly hostile environment as well as to serve as a guide to sexual renunciation.
Accepted: 2023-05-11T19:48:47Z
Keywords: 7th century; =CL; Aldhelm; Angleterre anglo-saxonne; Ascétisme; Christianism; Christianisme; Hagiographie; Hagiography; Martyr; Medieval history / Histoire médiévale (UMI : 0581); Monachisme; Saint; VIIe siècle; Virginité; anglo-saxon England; ascetism; exempla; monachism; virginity

Sauver l’enfant selon les récits de miracles au XIIIe siècles - Miller, Carolane (Université de Montréal, 2023)
Abstract This thesis focuses on the prevention of early childhood accidents in the Middle Ages. Through the study of three compilations of miracula, we will analyze the thematic of the child that they present. These compilations are the Miracles of the Blessed Virgin by Gautier de Coincy, the Miracles of Nostre-Dame de Chartres by Jean le Marchant and the Rosarius. In this study, we will look at the diversity of normative discourses surrounding this theme. These analyze allow us to take stock of the precautions surrounding children in the Middle Ages. We conclude that the Miracles of Nostre-Dame de Chartres are not representative of the general miracula corpus, cause the miracula it contains present a preventive character more focused on the physical dangers faced by the child.
Accepted: 2023-05-11T19:56:03Z
Keywords: =CL; Medieval history / Histoire médiévale (UMI : 0581); Middle Age; Moyen-Âge; Prévention; childhood; discours; enfance; hagiographie; hagiography; miracle; preaching; prevention; prédication; speech

La transformation poétique de Judith dans le poème en vieil-anglais "Judith" : de veuve pieuse juive à vierge héroïque anglo-saxonne - Lauzon, Nicolas (Université de Montréal, 2022)
Between the second half of the10th century and the beginning of the 11th century, the Old English poem Judith was written in one of the great monastic centers of the Anglo-Saxon world. This poem, based on the biblical text of the Book of Judith, is the result of the meeting of traditional biblical material and the heroic Anglo-Saxon poetic tradition. From this encounter emerges a work celebrating biblical history and the moral teachings it carries, as well as the values of Anglo-Saxon aristocratic culture and heroism. The poem Judith is therefore a strong example of cultural adaptation of biblical material. This thesis is concerned with this question of cultural adaptation, but even more with that of the coexistence of different traditions and cultural references within the Old English poem Judith. Throughout this thesis, it will be a question of determining the nature of this coexistence, namely how is it articulated? Does the poem present a case of hierarchization between these different cultural references? Or would it be fairer to speak of cultural pluralism and parallelism? Finally, how important is the historical context of the 10th and 11th centuries in the development of this poem? Following our analysis of the poem and its historical context we will demonstrate that Judith is a work of cultural parallelism where each cultural reference is presented without the need for hierarchy. In addition, we will demonstrate that the Judith is the result of changes in Anglo-Saxon society between the 9th and 11th centuries and the political and military instability caused by conflicts between Anglo-Saxons and Scandinavians.
Keywords: Anglo-Saxons; Anglo-saxon history; Anglo-saxon poetry; Heroic; Heroic poetry; Histoire anglo-saxonne; History - Medieval / Histoire - Médiévale (UMI : 0581); L'héroïque; Littérature médiévale; Medieval litterature; Old english poetry; Poésie anglo-saxonne; Poésie en vieil-anglais; Poésie héroïque; Syncretism; Syncrétisme; Viking

Les chartes de donations en Île-de-France au XIIe siècle : les exemples de l'abbaye Saint-Pierre-de-Montmartre et du prieuré Saint-Martin-des-Champs - Lavoie, Alex (Université de Montréal, 2019)
This thesis studies the charters of donations of two monastic establishments of the Ile-de-France in the twelfth century: the priory Saint-Martin-des-Champs and the abbey Saint-Pierre-de-Montmartre. This research concerning 160 ecclesiastical charters is based on the analysis of the social and religious relations that follows from the gifts offered by French royalty and aristocracy to these two monasteries. The overall objective is to highlight that the practice of donation plays a central role during medieval society and that it has engendered, perpetuated and consolidated religious and social interactions in linking them to the ideological framework of the ecclesia. The first stage of this research examines the anthropological and medieval historiographies of the gift and on the practice of donation in the Middle Ages. Then, we establish the historical context on the Île-de-France region during the reign of Louis VI, Louis VII and Philippe II, so between 1108 and 1223. The last step analyzes the practice of donating to The Middle Ages from a social point of view, among others the relations that are established by repeated donations between aristocratic families and the two monasteries under study. We also investigate the religious ideology surrounding the gift as a means of apprehending the salvation of the soul for the actors who, by this practice, are running the salutary spiritual mechanisms for their redemption. Finally, we address the global implications that affect the whole of medieval society, including public ceremonies and donation confirmations by the aristocratic and religious elite.
Keywords: Almsgiving; Aristocracy; Aristocratie; Aumône; Caritas; Church; Don; Don pro anima; Donation; Ecclesia; History - Medieval / Histoire - Médiévale (UMI : 0581); Paris; Pro anima's donation; Royalty; Royauté; Église; Île-de-France

Paysage religieux et ascétisme domestique dans les monachismes de la Gallaecia wisigothique - Lajoie, Kevin (Université de Montréal, 2024)
Après une période d’effervescence économique et de relative autonomie, les élites rurales de la Galice wisigothique se replient sur elles-mêmes durant la seconde moitié du VIIe siècle. À la suite de ce repli, de nouvelles formes de monachisme et d’ascétisme se repandent parmi les élites et les populations. Ces monachismes sont fermement ancrés dans leurs paysages religieux, lesquels ont été consolidés par les aristocrates depuis le IVe siècle. Par l’utilisation de sources littéraires et des résultats de récentes fouilles archéologiques sur des sites tels que Castromao dans Celanova ou encore Santas Augas, nous relevons les interrelations entre les aristocrates, la population locale, les autorités religieuses institutionnelles, les moines et les moniales, en portant une attention particulière au paysage religieux et les réalités imposées par les terrains accidentés des montagnes du nord-ouest de l’Hispanie. Il ressort de notre recherche que les ermites et les monastères s’appuyaient sur les traditions d’un lieu afin de mieux s’intégrer aux populations locales, avec lesquels ils entretenaient des relations dynamiques. Ce travail s’intéresse également à la transformation de communautés rurales en monastères. Ces transformations étaient souvent motivées par des désirs d’autonomie et de protection du patrimoine du groupe. Ces conversions éparpillées ont mené à une fédération d’abbés cherchant à s’unir sous une même règle, la regula monastica communis, qui cherche plus à assurer la cohésion interne de la communauté que sa rigueur spirituelle.
Accepted: 2024-04-30T17:42:17Z
Keywords: =CL

Se prosterner, pleurer, prier; la liturgie à travers les hagiographies féminines mérovingiennes - Timoteo, Patricia (Université de Montréal, 2025)
Malgré l’abondance d’études à propos de la liturgie féminine mérovingienne, la présente recherche a pour particularité de prendre les textes hagiographiques comme point de départ à sa réflexion. Nous tenterons alors d’analyser les limites de l’hagiographie féminine mérovingienne quant à la représentation de la liturgie qui est opérée, principalement, par les saintes et leur communauté. Aussi, nous entreprendrons de comprendre comment ces différentes formes de liturgie sont abordée dans les Vies. Pour ce faire, nous avons une démarche à la fois quantitative et qualitative. Une définition au sens large de la liturgie, et une lecture systématique des sources du corpus, nous a mené à pouvoir établir des micro et macro-catégories pour les différents actes et pratiques liturgiques se trouvant dans les Vies. Nous avons ensuite pu quantifier ces micro-catégories afin de nous pencher à la fois sur la fréquence de ces actes dans les Vies du corpus et sur la présence des gestes, larmes et émotions lors de la pratique liturgique. Le volet qualitatif, quant à lui, se concentre sur la place narrative des actes et pratiques liturgiques dans les Vies de notre corpus. Pour ce faire, nous avons repéré des éléments narratifs communs à toutes les Vies afin de pouvoir les étudier de manière simultanée. Ensuite, nous abordons l’efficacité liturgique des saintes en nous penchant sur les miracles. Pour finir, nous analysons l’apport du geste, des larmes et de l’émotion dans la pratique liturgique des femmes saintes et de leur communauté.
Keywords: =CL

Historiographie et discours normatif dans la société mérovingienne tardive : le cas du Liber Historiae Francorum - Dehaut, Catherine (Université de Montréal, 2025)
La présente étude s’articule autour du concept médiéval de l’historia et de la production hagiographique et historiographique qui s’y rattachait, dans la Gaule des VIIe et VIIIe siècles. La recherche récente sur les hagiographies politisées du VIIe siècle suggère que ces oeuvres pouvaient être porteuses d’une réflexion normative sur le système de valeurs et les comportements de l’élite dirigeante franque. Les stratégies mises en place pour assurer l’adhésion de l’audience aux propos des hagiographes, conjuguées à la fonction médiatrice de ces Vitae et à la conscience de l’autorité monastique qui s’en dégagent constituent le point de départ de la présente contribution. Celle-ci s’intéresse à un texte historiographique de la fin de l’époque mérovingienne, le Liber Historiae Francorum, et s’attache à déterminer dans quelle mesure un discours sur les normes sociales concernant l’exercice du pouvoir se manifeste aussi, dans cette mise en récit de l’histoire des Francs. Dans une approche stylistique comparative, l’analyse des stratégies narratives mobilisées par l’auteur du Liber Historiae Francorum, en parallèle avec d’autres textes historiographiques et hagiographiques mérovingiens, met en lumière les codes de comportements considérés comme désirables, au début du VIIIe siècle, au sein de l’élite dirigeante. Le Liber Historiae Francorum présente en effet des exempla de bons et de mauvais souverains, à travers la valorisation, dans les attitudes et comportements de ces personnages, des vertus chrétiennes et de certains idéaux de gouvernance. Une telle lecture d’un texte a priori historiographique permet d’ouvrir des pistes de réflexion concernant le rôle et l’influence qu’ont pu avoir certains monastères gaulois dans l’élaboration d’un discours normatif concernant l’exercice du pouvoir chez les Francs.
Keywords: =CL

Das Martyrium als Denkfigur: Brüche und Entwicklungslinien in christlicher Perspektive - Blennemann, Gordon; Herbers, Klaus (Vom Blutzeugen zum Glaubenszeugen ? : Formen und Vorstellungen des christlichen Matyriums im Wandel, 2014)
Section: 1 vol. (319 p.) ; 24 cm.

Continuities and Transformations in Hagiography - Blennemann, Gordon; Helvétius, Anne-Marie (Rethinking Reform in the Latin West, 10th to Early 12th Century, 2023)
Section: Rethinking Reform in the Latin West, 10th to Early 12th Century
Keywords: Church History; History; History of Religion; Medieval History; Religious Studies

Entre savoir profane et Révélation : la pratique exégétique à l’université d’Oxford 1229-1267 - Bellerose-Blais, Gabriel (Université de Montréal, 2019)
Through a study of the exegetical works of various masters associated with the University of Oxford between 1229 and 1267, we attempt to describe a freer environment than the one provided by the Université de Paris, which had prohibited the teaching of Aristotle’s libri naturales in 1210 and 1215. Robert Grosseteste, Richard Fishacre, Simon of Hinton and Roger Bacon articulate a conception of knowledge and the value of philosophical activity that seems to favour a more peaceful reception of the Greek philosopher, since the practice of literal exegesis legitimizes the speculations about nature to which this activity gives rise. This thesis attempts to understand the connections made by thinkers of the young University of Oxford, through their practice of exegesis, between Revelation and profane knowledge, and to see how their idea of theological inquiry evolved in the 13th century. We show that for the Oxford masters, answers to questions about Scripture are provided by natural philosophy and that all forms of profane knowledge, therefore, are seen as necessary, while always in the service of faith.
Keywords: Bacon; Fishacre; Grosseteste; History - Medieval / Histoire - Médiévale (UMI : 0581); Middle Ages; Moyen Âge; Oxford; Simon Hinton; exegesis; exégèse; natural philosophy; philosophie naturelle

Honneur et individualité : dynamiques identitaires dans les sagas des Islandais - Denis-Blais, Maxence (Université de Montréal, 2022)
This study aspires to place thirteenth-century Iceland more fully within the historiographical debate on the individual in the Middle Ages, which has tended to focus on continental Western Europe. It interrogates the perception that the ancient Icelanders had of themselves in relation to the notion of individualism. In turn, it seeks to identify the sustained relationship with the collective, to determine if the Icelanders could conceive and define themselves beyond group structures or membership. Analysis of the content of the sagas of Icelanders (Íslendingasögur), a literary genre specific to Iceland, makes it possible to formulate a history of mentalité for this purpose. The notion of honor, a central theme in the texts, serves to evaluate the degree of individuality accorded the ancient Icelanders. The various dimensions of honor as expressed in the sagas are then dessected to answer this question. Honor is first considered in its relation to reputation. The importance of the idea of reputation as well as the process by which it is established is then observed. Analysis of how honor and its pursuit are motivating themes in the sagas are then considered. Finally, honor is perceived under the theme of the perception of oneʼs dignity and its social implications.
Keywords: Collectif; Collective; Dignity; Dignité; History - Medieval / Histoire - Médiévale (UMI : 0581); Honneur; Honor; Iceland; Identity; Identité; Individu; Individual; Islande; Middle Ages; Moyen Âge; Reputation; Réputation; Saga; Scandinave; Scandinavian

Le modèle de la vierge consacrée au VIe siècle : l’exemple du De consolatoria castitatis laude d’Avit de Vienne - Domingos Pimentel, Caroline (Université de Montréal, 2020)
In the 6th century, in the kingdom of the Burgundians, Avitus of Vienne composes a letter for his sister, the nun Fuscina. This consoling and eulogistic artwork is called De consolatoria castitatis laude. This text generates in us an understanding of the particular context of the virgo in the Christian society of Late Antiquity. Regarding the text, the purpose of the book is to show to the monacha that the virginal choice represents a way of escape and freedom, a reality that the spouse is unaware of. The duties of marriage, the dangers of motherhood, the troubles of the century, the widowhood and the mourning are all unknown to the virgin because she excludes herself to worldly obligations. The use of the Bible and several patristic references shape the legacy of religious mentalities which inspires Avitus in making an oriented speech on the virgo’s socio-religious distinctness.
Keywords: Ambroise de Milan; Ambrose of Milan; Asceticism; Ascétisme; Augustin; Augustine; Avit de Vienne; Avitus of Vienne; Bible; Chasteté; Chastity; Christian perfection; Female monasticism; Hagiographie; Hagiography; Histoire des femmes; Histoire des mentalités religieuses; History - Medieval / Histoire - Médiévale (UMI : 0581); History of religious mentalities; Idéologies patristiques; Jerome; Jérôme; Monachisme féminin; Patristic ideologies; Perfection chrétienne; Tertullian; Tertullien; Virginity; Virginité; Women’s history

Genre, mémoire et histoire dans le monastère San Salvatore/Santa Giulia à Brescia, VIIIe-IXe siècles - Grimard-Mongrain, Rosalie (Université de Montréal, 2019)
Although the field of memory studies is well-developed in medieval history, the role of gender in the construction of memory is only just beginning to be integrated. This M.A. thesis considers the relationships among gender, memory and history at the monastery of San Salvatore/Santa Giulia in Brescia (ca. 8th and 9th centuries). These three concepts help to expand our understanding of the place memory occupied in the monastery and its historical context, a function reinforced by the primacy of monasteries in the management of memory and the crafting of history within the Carolingian Empire. The Liber memorialis is the primary source for this study. The document, written from 856, contains lists of names of persons belonging to the prayer community and liturgical texts. It transmits ritual practices related to intercession for the dead as well as the names of people who are part of the abbey’s prayer community. We also seek to understand how the Liber memorialis served as a means to craft representation and the perpetuation of different levels and logics of real and ideal communities: the local and imperial aristocracy, the imperium, and the ecclesia. In this study, we will place the Liber memorialis of Brescia within the wider ideological context of time.
Keywords: Carolingian Empire; Communautés; Communities; Early Middle Ages; Empire carolingien; Gender; Genre; Haut Moyen Âge; Histoire; History; History - Medieval / Histoire - Médiévale (UMI : 0581); Italie du Nord; Memory; Monachisme; Monasticism; Mémoire; Northern Italy; Prayer of intercession; Prière d'intercession

Ancrer l'héritage carolingien dans l'Empire germanique : analyse historique de la Vie de Chrodegang de Metz - Goupil-Warmoes, Laurie (Université de Montréal, 2026)
Au Xe siècle, le Royaume germanique connaît, sous la dynastie des Ottoniens, d’importantes transformations politiques et religieuses. La continuité par rapport aux traditions impériales antérieures, notamment l’Empire carolingien, est un enjeu au cœur de ces transformations. En 962, le royaume devient en effet Empire par le couronnement impérial d’Otton Ier. Dès les années 30 du Xe siècle, l’intégration de la Lotharingie donnait une réalité territoriale au lien idéologique entre l’Empire carolingien et l’Empire en construction des Ottoniens. En tant que lieu de mémoire important des temps carolingiens, la ville et le diocèse de Metz s’imposent alors comme contexte de réflexion sur ces logiques de continuité, animée surtout par les évêques messins en tant qu’acteurs politiques de premier ordre de leur temps, tout particulièrement des figures épiscopales comme Adalbéron Ier, Thierry Ier et Adalbéron II. Ce mémoire propose une analyse d’un produit majeur de cette dynamique de réflexion sur les liens entre le passé carolingien et le présent ottonien : la Vie de Chrodegang de Metz, évêque réformateur du VIIIe siècle et acteur majeur des débuts de la dynastie carolingienne. L’analyse souhaite avant tout comprendre comment l’hagiographe exploite la mémoire de Chrodegang pour donner un sens à des enjeux politiques et religieux de la deuxième moitié du Xe siècle, aussi bien dans le cadre du diocèse de Metz que celui de l’Empire ottonien : le rôle des évêques dans le système de l’Église impériale, les réformes monastiques, les rapports entre l’Empereur et le pape ou encore le culte des reliques.

Papsttum und Orden in der Interaktion. Beobachtungen und Perspektiven zur begrifflichen Einordnung - Blennemann, Gordon; Andenna, Cristina (Die Ordnung der Kommunikation und die Kommunikation der Ordnungen. Bd. 2 Zentralität: Papsttum und Orden im Europa des 12. und 13. Jahrhunderts, 2012)
OCLC: ocn845099532
Keywords: Communication; Communication systems History; Congresses; History; Monasticism and religious orders; Papacy

Liturgy and Female Monastic Hagiography Around the Year 1000: A lecture croisée of the Life of Liutrud, the Second Life of Glodesind of Metz and the So-called Pontificale Romano-Germanicum - Blennemann, Gordon (Women and Monastic Reform in the Medieval West, c.100-1500 Debating Identities, Creating Communities, 2023)
In a fundamental essay published in 1991 on the significance of religious women’s communities in early and high medieval Saxony, the late Michel Parisse called for a comparative perspective on the political, social and religious conditions of the conspicuous density of women's communities in Saxony. In doing so, he referred to his home region of Lorraine, for which he – amongst others – used the term Lotharingia to describe its early medieval reality. In terms of sheer numbers, Lotharingia is indeed closest to the Saxon situation, but chronologically its monasteries also refer back to earlier times. Examples of this are the Merovingian foundations of Remiremont in the Vosges and Sainte-Glossinde and Saint-Pierreaux- Nonnains in the Carolingian lieu de mémoire Metz. Women's monasteries like these combined stabilising power in the Carolingian core lands with supra-regional influence within the framework of the Frankish regnum and imperium. For areas such as Saxony, which were integrated comparatively late into the Frankish sphere of influence, the politico-religious structures of the ancient parts of the Frankish realm provided a framework of tradition and reference far into the post-Carolingian period. In this contribution – not least as an expression of gratitude to one of my academic teachers – I would like to take up Parisse's observations. I do not aim at a similarly broad investigation, especially since a comparative approach in a broad thematic perspective would go beyond the scope of the contribution as well as of this volume, even though recent studies on women's religious communities in Saxony and Lorraine invite us to do so. The focus is rather on a partial aspect: the textual and ideological relations between liturgy and hagiography in the tenth and early eleventh centuries. Such an approach is complementary to studies in which the importance of relics and hagiographical texts as vectors of communication, the transfer of ideas and the spatial integration of new secular and ecclesiastical structures of power were elaborated – again primarily for the Carolingian period. Following on from these studies, the observations in this article concentrate on religious and monastic aspects of these genres and raise questions about the shared significance of liturgy and hagiography for the definition and mediation of traditional as well as new ascetic and monastic models of life in the tenth century. The debates which shaped these models are part of monastic and broader religious transformations traditionally labelled as the reform of the tenth and early eleventh century.

Heiligkeit und Devianz in vormodernen Kontexten : Perspektiven einer möglichen Systematisierung - Blennemann, Gordon (Sakralität und Devianz : Konstruktionen – Normen – Praxis, 2015)
Section: 1 vol. (314 p.) : Ill. ; 24 cm.

Konstanz und Wandel : religiöse Lebensformen im europäischen Mittelalter - Blennemann, Gordon; Kleinjung, Christine; Kohl, Thomas (Didymos-Verlag, 2016)
Section: 1 v. (280 pages) : illustrations ; 25 cm

« Ehrliche Kriegsleute » : la construction de la représentation du lansquenet au royaume de France lors de la Renaissance (1486-1559) - Handfield, Nicolas (Université de Montréal, 2019)
Through an approach that seeks to link the question of the culture of war to the awareness of the social, economic and political dimensions of war, this study highlights the construction of the figure of the landsknecht through the prism of the practices of these German mercenaries and the representations of French contemporaries. To identify this dominant figure of the Renaissance, it is a question of circumscribing the strategies implemented by the lansquenets, i.e. the arsenal of symbols, speeches and behaviours to which the members of this group refer, and to confront them with the discourses of the French military and civilians in order to apprehend the perception they have of the landsknechte and the behaviours they develop towards them. The dialectic between the practices of the Lansquenets and the French representations of them illustrate the profound transformations of the French monarchy at the dawn of the Modern Era and reveals a society's apprehension of alterity.
Keywords: Culture; Foreigner; History - Military / Histoire - Militaire (UMI : 0722); Identity; Identité; Landsknecht; Lansquenet; Mercenaire; Mercenary; Monarchie; Monarchy; Representation; Représentation; Violence; Étranger

«La laïcisation des études médiévales» : l’Institut d’études médiévales de l’Université de Montréal et sa réforme académique de la Révolution tranquille, 1959-1968 - Robert, Martin (Université de Montréal, 2022)
This master's thesis analyses the institutional transformations of the Institut d'études médiévales of the Université de Montréal between 1942 and 1968. To do so, we focus on the effects of the Quiet Revolution on the Institut d'études médiévales, an institution of higher learning founded by the Dominican Order in 1930. Inspired by the Nouvelle Théologie outlined by Marie-Dominique Chenu, the Institute embraces a doctrinal raison d'être and uses scientific know-how to achieve it. By adapting the historical-critical method to infer the teaching of Thomism, the Institute represents an interesting religious-scientific amalgam to understand the effects of the secularization of the Université de Montreal on its structures, its culture, and its institutions. We describe the journey of this institution through La Grande Noirceur, the Quiet Revolution, and the secularization of the university’s Charter. Through the analysis of the archives of the Université de Montreal and the Canadian Province of the Dominican Order, we describe the institutional history of the Institut d'études médiévales according to the evolution of its hopes and of its functions at the university. Through the analysis of its mission statements, we describe how the Institute adapts to keep pace with the structural and cultural evolution within Quebec’s Quiet Revolution.
Keywords: Analyse du discours; Center for Medieval Studies; Centre d’études médiévales; Discourse analysis; Faculty of Arts and Sciences; Histoire des universités; Histoire institutionnelle; History - Canadian / Histoire - Canadienne (UMI : 0334); History of universities; Institut d’études médiévales; Institute of Medieval Studies; Institutional history; Laïcisation; Nouvelle théologie; Philosophie; Philosophy; Quiet revolution; Révolution tranquille; Secularization; University of Montreal; Université de Montréal

Venantius Fortunatus, Vita Radegundis - Blennemann, Gordon (Le légendier de Turin : ms. D.V.3 de la Bibliothèque nationale universitaire, 2014)
Section: 891 pages : illustrations + 1 DVD-ROM

Raumkonzept und liturgische Nutzung: Eine Spurensuche zur Frühgeschichte der Metzer Frauenklöster Sainte-Glossinde und Saint-Pierre-aux-Nonnains - Blennemann, Gordon (Frauen-Kloster-Kunst: Neue Forschungen zur Kulturgeschichte des Mittelalters Beiträge zum Internationalen Kolloquium vom 13. bis 16. Mai 2005, anlässlich der Ausstellung "Krone und Schleier", 2007)

Vorbemerkungen: Zentralität als geographischer, mentaler und virtueller Begriff - Herbers, Klaus; Melville, Gert; Blennemann, Gordon (Die Ordnung der Kommunikation und die Kommunikation der Ordnungen. Bd. 2 Zentralität: Papsttum und Orden im Europa des 12. und 13. Jahrhunderts, 2013)
Num Pages: 331

Ascetic Prayer for the Dead in the Early Medieval West - Blennemann, Gordon (The Cambridge History of Medieval Monasticism in the Latin West, 2020)

Basilica-monasterium: A Comparative Study of the First Holy Sites of Western Christianity, c. 400-c. 900, I - Blennemann, Gordon; Helvétius, Anne-Marie; Veronese, Francesco (2023 International Medieval Congress, 2023)
Historiography of ancient monastic trends has been deeply renewed during the recent years thanks to several conferences which put forward comparative and interdisciplinary approaches, some of them being specifically dedicated to female forms of religious life. Henceforth, scholars dissuade us to read the history of monasticism trough 'Benedictine glasses'. They invite us to take into account every type of sources - written, archaeological, iconographic, epigraphic. The interpretation of the written sources - monastic rules, but also hagiographical and diplomatic sources - has been nowadays deeply renewed. These recent works agree to give to early 'monasticism' a wider definition, taking into account the extreme diversity of the community forms of religious life attested in the West during this period. These works deserve to be continued further through comparative studies focused on precise problematics. This research project aims to explore how some communities tried to reconcile the practice of a monastic life with the service of an important sanctuary, and also how some ancient communities succeeded in holding firm through centuries, often with the support of powerful protectors.

Les politiques de gestion de crises de Charles le Chauve en marche d’Espagne et de Bretagne : comparaison d’espaces politiques troubles - Havard-Trépanier, Geoffrey (Université de Montréal, 2021)
Charles the Bald’s reign was a period of political and ideological transformations for the carolingian royalty. The troubles with the Breton and Spanish march along with the external raids are probably the sources of tension which have captured the most attention from medievalists. The so-called armorican emancipatory quest or the personal and familial ambitions of the septimanian and iberian magnates are still cited as evidences of the weakening of Carolingian political power following the 843 treaty of Verdun. By focusing on the king’s conflict resolution policies in these two territories, apparently hostile to his power, this study wants to establish wheter the tensions in the marches were as complex and irremediable as the primary sources suggested. By comparing the field policies visible in the royal charters, we noticed that theses troubles were not fundamentally different from those present elsewhere in the kingdom. The strategies employed by the king shows that the royalty had the means to overcome these obstacles and to affirm his political supremacy. Noticeably, these oppositions do not seem to be so particular. The political and economic issues that they were impliying were reflecting the main political concerns of the Carolingian kings following the 840-843 civil war. It was important to them to promote their divine legitimacy as well as appearing as the only political choice for the kingdom’s elites.
Keywords: Actes royaux; Breton march; Carolingian State; Carolingian elites; Carolingian politics; Charles le Chauve; Charles the Bald; Comparatisme historique; Comparative History; Francie occidentale; Haut Moyen-Âge; High Middles-Ages; History - Medieval / Histoire - Médiévale (UMI : 0581); Marche de Bretagne; Marche d’Espagne; Politique carolingienne; Royal charters; Spanish march; West Francia; Élites carolingiennes; État carolingien

Martyre et prédication. Adaptations d’un modèle hagiographique dans les sermons de Césaire d’Arles - Blennemann, Gordon (Normes et hagiographie dans l'occident latin, VIe-XVIe siècles: actes du colloque international de Lyon 4-6 octobre 2010, 2014)

San Salvatore/Santa Giulia à Brescia : un monastère de femmes et sa liturgie (VIIIe-Xe siècles) - Grimard-Mongrain, Rosalie (Université de Montréal, 2024)
Bien que plusieurs études aient été consacrées aux Libri memoriales, à l’exemplaire de Brescia et au monastère San Salvatore/Santa Giulia, aucune monographie n’a replacé le Liber memorialis au cœur de l’histoire de la communauté monastique qui l’a créé. Cette thèse propose d’utiliser ce manuscrit, conçu en 856 et composé de listes de noms et de textes liturgiques, pour analyser les réseaux et la liturgie entre 750 (décennie de la fondation du monastère) et 1000 (l’emprise des Ottoniens sur l’Italie). Les listes de noms témoignent des relations des moniales au sein de leur propre communauté et avec les institutions de la cité épiscopale de Brescia : l’évêque et le clergé de la cathédrale. Ces listes illustrent également le réseau des moniales à l’extérieur de la ville — au niveau local, transalpin et impérial — et avec divers groupes : les parents des moniales, les nobles, les clercs, les évêques, les moines et les moniales et enfin, les pèlerins. L’objectif est aussi de s’interroger sur le rôle de la liturgie comme créatrice de liens entre ces divers groupes et sur l’agentivité des moniales dans la mise en place et la pérennisation de ces réseaux de même que dans la pratique de la liturgie. Outre le Liber memorialis, une grande variété de sources liées ou produites par les moniales de San Salvatore/Santa Giulia a été mobilisée dans cette recherche : des sources diplomatiques (diplômes, chartes et privilèges), des sources hagiographiques et des hymnes, des sources liturgiques de la seconde moitié du Moyen Âge (Psautier-Collectaire et Ordinaire) ainsi que des sources matérielles. L’ensemble de ces ouvrages permet d’appréhender comment les moniales concevaient leur communauté. Ma recherche souhaite également développer une réflexion sur le rôle du Liber memorialis au sein de la communauté de moniales et pour les gens qui y faisaient inscrire leur nom de même que sur le caractère distinct de l’exemplaire de Brescia par rapport aux autres Libri memoriales. Mon hypothèse est que le manuscrit de Brescia représentait une communauté imaginée dont le socle était les moniales de San Salvatore/Santa Giulia, caractère accentué dans le Liber memorialis de Brescia par le regroupement de listes de noms et de textes liturgiques dans un même codex.
Accepted: 2024-10-11T18:02:04Z
Keywords: =CL

Die Ordnung der Kommunikation und die Kommunikation der Ordnungen. Bd. 2 Zentralität: Papsttum und Orden im Europa des 12. und 13. Jahrhunderts - Andenna, Cristina; Blennemann, Gordon; Herbers, Klaus; Melville, Gert (Franz Steiner Verlag, 2013)
Das Papsttum und die vita religiosa, die Welt der Klöster und Orden, sind die beiden einzigen institutionellen Lebensformen des Mittelalters, die für sich eine eigene universelle Geltung beanspruchen konnten. Durch die Ausbildung komplexer kommunikativer Strukturen und innovativer Organisationsformen nahmen beide vor allem seit dem 12. und 13. Jahrhundert Anteil an der Grundlegung eines "Kulturraums Europa".Vor diesem Hintergrund stand der analytische Vergleich von Papsttum und vita religiosa als aufeinander bezogene Kommunikationssysteme im Mittelpunkt zweier Tagungen am Deutsch-Italienischen Zentrum für Europäische Exzellenz der Villa Vigoni, deren Ergebnisse nun in einer zweibändigen Publikation vorliegen.Die Beiträge des zweiten Bandes widmen sich der Rolle der römischen Kurie bei der überregionalen Vermittlung religiöser Normen und kultureller Werte als universal gedachte Ordnungsvorstellungen und fragen zugleich nach dem Anteil der religiösen Orden an diesen Vermittlungsprozessen.
Pages: 331
Keywords: Europa; Geschichte; Kommunikation; Papsttum

Hagiographie : une norme narrée. Regards sur les Vitae de Jutta de Sponheim et d’Hildegarde de Bingen et le Liber visionum d’Élisabeth de Schönau - Blennemann, Gordon (Enfermements. II, Règles et dérèglements en milieu clos (IVe-XIXe siècle), 2015)
D'évidence, il n'y a pas d'enfermement sans règle. L'un des traits communs aux mondes clos est que ceux qui y vivent doivent obéir à des normes fortes, qu'il s'agisse de la règle monastique, de la règle hospitalière ou du règlement de prison. Reprenant l'étude comparée des enfermements religieux et carcéraux esquissée par les sciences sociales dans les années 1960 et 1970, le présent ouvrage, qui fait suite au volume Enfermements. Le cloître et la prison (VIe-XVIIIe siècle) publié en 2011, explore la place que prennent les règlements et les normes dans les cloîtres comme dans les prisons. Par une méthode comparée systématique, il montre toutes les nuances de cette histoire sur la longue durée, entre ive et XIXe siècles, et dans toute l'Europe, des Iles Britanniques à la péninsule ibérique. À cet effet, il interroge la nature de la règle et historicise sa mise en texte, avant de comparer les modes de production de l'obéissance et les dérèglements qui surgissent dans les milieux clos. L'un des enjeux de cette étude comparée des règles et dérèglements en milieux clos est de comprendre et de réévaluer le rôle que la discipline régulière religieuse a pu jouer dans la mise en place des systèmes carcéraux occidentaux
Section: 459 pages ; 24 cm.

Die Darstellung und Deutung des Räumlichen im hagiographischen Dossier der Hl. Glodesindis, Äbtissin in Metz (BHL 3562–3564) - Blennemann, Gordon (Heilige, Liturgie, Raum, 2010)
OCLC: ocn642845040
Keywords: Christian saints; Congresses; Cult; Liturgies; Sacred space; Sanctification; Worship